Deleuze and the social - Fuglsang, Martin; Sørensen, Bent Meier (Deleuze connections., 2006)
Deleuze and the Social is the first book to focus on the implications of Gilles Deleuze and FÃ♭lix Guattari's thinking on the social sciences and organisation. This book is concerned with the most basic notions of 'the social'. It seeks both to comprehend the 'multiplicity' of the social - in Deleuzian terms, the 'becoming' of the social itself; and it seeks to develop a new social analytical practice. Each of the newly commissioned chapters aims to show the strength of as well as practice the radicalism of a Deleuzian and Guattarian approach to social science and organisation studies. Deleuze and the Social is a book about order, subjectivity, art, capitalism and the construction of a social ontology. It avoids scholasticism by foregrounding its authors' shared concern for practical issues. How is social order constituted? How is resistance possible between the rush of capitalism and the overcoding of the State? How are thinking and living possible? Deleuze and the Social raises these questions and many more. The international team of authors includes Eric Alliez, Maurizio Lazzarato, Eugene Holland, Paul Patton, Manuel DeLanda and Ian Buchanan.